Examining the Relationship between School Leadership Styles and Organizational Culture in Secondary Schools (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In his capacity as the leader of the organisations, it is imperative that he possesses acomprehensive readiness across all facets and circumstances. The primary objective of this investigationwas to examine the following The topic of discussion pertains to the leadership exhibited by schooladministrators operating within the purview of the Office of Secondary Education Service Area 20. Theefficacy within educational institutions. The objective of this study is to examine the correlation betweenleadership styles and the level of effectiveness in educational institutions. The present investigationemployed a research design characterized by the utilization of correlation analysis. The population underconsideration consisted of 2,788 individuals affiliated with the office of Secondary Educational ServiceArea 20, encompassing the subsequent constituents There are a total of 160 administrators and 2,628teachers in the given context. The table was employed for the purpose of determining the appropriatesample size. The utilization of Stratified Random Sampling was also employed in order to procuresamples that were drawn based on the size of the respective schools. The total number of samplescollected for this study amounted to 451, comprising 113 individuals who held positions as schooladministrators and 338 individuals who were employed as teachers.